2023
DOI: 10.3390/plants12233968
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Culture Conditions and Plant Growth Regulators for In Vitro Callus Induction and Plant Regeneration in Paeonia lactiflora Pall.

Wenhui Song,
Yaohong Song,
Xueting Liu
et al.

Abstract: Owing to its high ornamental, medicinal and horticultural values, herbaceous peony (Paeonia lactiflora Pall.) has been widely used as a landscaping and economical plant around the world. However, the lack of an efficient and stable regeneration system in P. lactiflora restricts its rapid propagation and large-scale production. By testing the key factors affecting callus formation, proliferation, adventitious bud induction and rooting, here, we developed an in vitro system for callus induction and regeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…This result is consistent with those reported by other researchers regarding the essential role of auxins in plant propagation by cuttings [52][53][54][55][56]. IBA was found to be the most effective in vitro rooting regulator of all three auxins studied, in agreement with results from other studies (57)(58). The results revealed that as the amount of auxin in the culture medium increased, the formation of calluses at the base of micro-shoots occurred.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with those reported by other researchers regarding the essential role of auxins in plant propagation by cuttings [52][53][54][55][56]. IBA was found to be the most effective in vitro rooting regulator of all three auxins studied, in agreement with results from other studies (57)(58). The results revealed that as the amount of auxin in the culture medium increased, the formation of calluses at the base of micro-shoots occurred.…”
Section: Discussionsupporting
confidence: 92%
“…For Populus trichocarpa , a cytokinin/auxin ratio of 5/1 resulted in the highest bud induction rate ( Ma et al., 2022 ). However, the specific ratios and intensities of these hormones have not been clearly determined across different plants, and varying these ratios with different hormone strengths can lead to dramatically different outcomes ( Song et al., 2023 ). We observed both high and low induction rates at a 6-BA/NAA ratio of 3/1.…”
Section: Discussionmentioning
confidence: 99%